Prestressed Concrete T-Beams Strengthened with Near-Surface Mounted Carbon-Fiber-Reinforced Polymer Rods Under Monotonic Loading: A Finite Element Analysis - Laurencius Nugroho; Yanuar Haryanto; Hsuan-Teh Hu; Fu-Pei Hsiao; Gandjar Pamudji; Bagus Hario Setiadji; Chiao-Ning Hsu; Pu-Wen Weng; Chia-Chen Lin (Eng)
Prestressed concrete structures, designed to enhance the compressive strength of concrete through internal pretension, are increasingly susceptible to serviceability issues caused by rising live loads, material degradation, and environmental impacts. Strengthening or retrofitting offers a practical and cost-effective alternative to full replacement. This study investigated the flexural strengthening of prestressed concrete T-beams in the negative moment region using near-surface mounted (NSM) carbon-fiber-reinforced polymer (CFRP) rods. Validation against experimental results from the literature demonstrated high accuracy, with an average numerical-to-experimental ultimate load ratio of 0.97 for reinforced concrete T-beams strengthened with NSM-CFRP rods, a negligible difference of 0.49% for prestressed concrete I-beams, and a minimal error of 1.30% for prestressed concrete slabs strengthened with CFRP laminates. Parametric studies examined the effects of CFRP rod embedment depths and initial prestressing levels. In certain cases, achieving the minimum embedment depth is not feasible due to design or construction constraints. The results showed that fully embedded CFRP rods increased the ultimate load by up to 14.02% for low prestressing levels and 16.36% for high levels, while half-embedded rods provided comparable improvements of 11.20% and 15.76%, respectively. These findings confirm the effectiveness of NSM-CFRP systems and highlight the potential of partial embedment as a practical solution in design-constrained scenarios.